El nuevo desarrollo reglamentario del Procedimiento de Inspección Tributaria (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2008)
On January 1st 2008, it took effect the new regulation on tax procedures, approved by the national government in July 2007. This regulation includes the new rules on tax audit procedures, repealing the former regulation on this subject. The author analyses the main new issues included in this norm. This analysis reveals that, although the most important issues had already been changed by the General Tax Law, approved by the parliament in 2003, the new regulation includes some major changes in the way certain steps of the procedure must be understood.